A study on the cognitive dysfunctions in spouses of patients with alcohol dependence syndrome - Rinet Sonia Dsouza; Satish Kumar; John P Mathai (Wolters Kluwer Medknow Publications, 2015)
Context: Alcoholism is a disease of the family. Alcoholism is linked to disrupted family role, violence, impaired family communication and physical and psychological illness. Several studies have shown that spouses of alcoholics often present significant rates of mental and physical problems, communication problems, low social activity and poor marital satisfaction. The inconsistent results from previous research clearly demonstrate the need for more evidence. Aims: To study the cognitive dysfunctions in the spouses of patients with alcohol dependence syndrome (ADS). Settings and Design: The data were collected from 30 spouses of patients admitted at the deaddiction centre and psychiatry ward of Father Muller Medical College Hospital Mangalore. Materials and Methods: Samples were selected from spouses of patients admitted consecutively, who met inclusion and exclusion criteria. Samples of the study were evaluated using Standardized Mini Mental State Examination (SMMSE), Trail Making Test B (TMT-B), Digit Symbol Substitution Test (DSST). Statistical Analysis Used: Conventional statistics were used to calculate mean and standard deviation (SD) for the parameters of the study. Results: It was found that 26.6% of the spouses were cognitively impaired showing decreased, impaired cognitive functions, of which 62.5% had history of alcohol consumption of the spouses for 6-10 years of duration. Conclusions: Study proved the decrease in cognitive functions in the spouses of patients with alcohol dependence syndrome.